2015
DOI: 10.1016/j.optmat.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A high efficiency rare earth-free orange emitting phosphor

Abstract: This communication provides a brief summary on rare earth (RE)-based and RE free-based nitrides and oxynitride phosphors reporting for the first time the photoluminescence quantum yield (PLQY) of a highly emissive AlN:Mn 2+ obtained at relatively low temperatures. The PLQY of the AlN:Mn emitter was measured to be 82%, a value among the highest measured for non-RE phosphors. . Though the AlN matrix shows an emission peak at a similar position to the emission peak observed for AlN:Mn product, the Mn-containing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Due to this, the design of rare-earth free materials is majorly needed. The rare-earth free phosphors can be understood with three main strategies: (i) use of transition metals for luminescent centers171819202122, (ii) use of defects such as oxygen vacancies23242526 and (iii) use of materials such as tungstates and vanadates27282930.…”
mentioning
confidence: 99%
“…Due to this, the design of rare-earth free materials is majorly needed. The rare-earth free phosphors can be understood with three main strategies: (i) use of transition metals for luminescent centers171819202122, (ii) use of defects such as oxygen vacancies23242526 and (iii) use of materials such as tungstates and vanadates27282930.…”
mentioning
confidence: 99%
“…Generally, these properties could be improved by better crystallization and purifying materials. Current challenges on phosphors research to obtain desired phosphors for lighting application is briefly reviewed in Table 1 respectively on luminescent features and high quantum efficiency [2][3][4][5][6][7], reduced of RE usage for host phosphor [8][9][10][11][12][13][14][15][16][17], morphology and size [18][19][20][21][22][23][24][25][26][27][28][29][30], preparation/synthesis methods [9,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], and new phosphors …”
Section: Phosphor For Lighting Applicationsmentioning
confidence: 99%
“…Since several raw material of phosphors are highly demanding material, in turn the price increases. Therefore effort on replacing rare earth materials as host phosphors currently intense research was conducted to gain a non RE-based host phosphor [8][9][10][11][12][13][14][15][16][17]. However, some of them still use RE as doping element.…”
Section: Phosphor For Lighting Applicationsmentioning
confidence: 99%
“…The strong afterglow reported previously for both undoped [18] and doped AlN phosphors [17] is consistent with the UV absorption populating the conduction band of AlN, and the subsequent delayed luminescence resulting from the presence of shallow traps (likely nitrogen vacancies). Other recent studies have found that AlN:Mn is an excellent cathodoluminescent phosphor [9], and reported emission efficiency of ~80% with 320 nm excitation [21]. There are no prior published studies of the use of AlN phosphors in a mercury discharge lamp, which is the focus of this paper.…”
Section: Introductionmentioning
confidence: 95%